2014
DOI: 10.4028/www.scientific.net/amr.893.430
|View full text |Cite
|
Sign up to set email alerts
|

Wear and Frictional Behaviour of Metals

Abstract: Abstract. In the current study, wear and frictional performances of different metals are investigated under different operating parameters against stainless steel counterface under dry contact conditions. The experiments performed using block on ring machine. Microscopy was used to examine the damage features on the worn surface and categorize the wear mechanism. Thermal imager was used to understand the thermal loading in the interface during the rubbing process. The results revealed that the operating parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…Aluminium, being a light metal, was influenced at smaller loads. Previous studies and literature review suggest that the fluctuations in such frictional behavior occur because of transfer of materials from one surface to another (Sahin et al, 2007;Alidokht et al, 2012;Alotaibi et al, 2014a). Comparing the frictional values for all three metals, at 30N applied load, it is found that copper exhibit the highest friction coefficient than others.…”
Section: Resultsmentioning
confidence: 79%
“…Aluminium, being a light metal, was influenced at smaller loads. Previous studies and literature review suggest that the fluctuations in such frictional behavior occur because of transfer of materials from one surface to another (Sahin et al, 2007;Alidokht et al, 2012;Alotaibi et al, 2014a). Comparing the frictional values for all three metals, at 30N applied load, it is found that copper exhibit the highest friction coefficient than others.…”
Section: Resultsmentioning
confidence: 79%
“…The complexity of predicting the wear and frictional performance of the materials motivates the tribologist to adopt an artificial neural network (ANN) approach, as it can be used to make such predictions with caution [7]. With the requirement for accuracy in modelling the behaviours of lubricants becoming more crucial, a sophisticated constitutive model needs to be developed.…”
Section: Introductionmentioning
confidence: 99%
“…Artificial neural network modelling was employed by Idoko et al, [8] to predict Viscosity index and specific heat capacity of grease lubricant produced from selected oil seeds. Jasem Alotaibi [7], examined the accuracy and prediction performance of artificial neural networks (ANNs) for friction, wear, interface temperature and roughness of metal/metal adhesive wear.…”
Section: Introductionmentioning
confidence: 99%